The Ethics of “Commercial Bribery”: Integrative Social Contract Theory Meets Transaction Cost Economics - Johnsen, D. Bruce (Journal of business ethics, 2009)
This article provides an ISCT analysis of commercial bribery focused on transaction cost economics. In the language of Antitrust, commercial bribery is a form of vertical arrangement subject to the same efficiency analysis that has found other vertical arrangements potentially beneficial to consumers. My analysis shows that actions condemned as commercial bribery in the Honda case (1996) may well have benefited Honda’s dealer network once promotional free riding and other forms of rent seeking by dealers are considered. I propose that the term “commercial bribery” should be avoided until after an ISCT analysis shows that the community is likely to have been harmed. The term “third-party payments” is a more ethically neutral term with which to begin the analysis.